PUASA RAMADHAN MEMBENTUK KARAKTER ANAK SEJAK DINI - Enny Nazrah Pulungan (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Ramadhan fasting is a compulsory worship for Muslims. This worship has to be introduced to the children since their childhood. Starting from recognizing and the meaning of fasting, the children will slowly learn to fasting in several stages until they are considered capable to do fasting. Islam instructs children to get used to doing their obligations from an early age. Ramadhan is a very good month for parents to instill positive character to their children. Every parent want their children to become human beings who are not only intellectually intelligent. But also emotionally and spiritually intelligent. Building their character ideally starts from their early age, because at that age understanding of concepts and planting good values is easily given to them through habituation and parental example. At that age, childrens are also not so much influenced by theie surrounding environment. Because in the fasting of Ramadhan contains a lot of wisdom, including being able to instill a positive character in children, religious, honest, patient, responsibility, caring, sympathy for others, etc.Kata kunci: fasting, character, early age.